1979
DOI: 10.1002/bjs.1800660607
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis in Hong Kong

Abstract: A series of 311 Chinese patients with acute pancreatitis admitted to Queen Mary Hospital, Hong Kong, over a 10-year period is reviewed. Biliary tract disease was associated with pancreatitis in 52.4 per cent of patients and 77.9 per cent of them had stones, mud or parasites in the common bile duct. Fever and jaundice were present in 55 per cent and 41.2 per cent of patients respectively. Because of the prevalence of recurrent pyogenic cholangitis among the indigenous population, emergency operation, with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Early LC or early open cholecystectomy as the procedure of choice in patients with mild ABP is also supported by other studies [ 1, 8, 12, 14 ]. In contrast, a number of studies [ 3, 10, 13, 15, 16 ] have suggested deferring surgery until 6–8 weeks, because they found an increase in procedure and anaesthesia‐related morbidity and mortality in these patients. The problem in many of these studies was that all patients were taken up for surgery irrespective of their Ranson scoring and thus included even those patients who had severe disease.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Early LC or early open cholecystectomy as the procedure of choice in patients with mild ABP is also supported by other studies [ 1, 8, 12, 14 ]. In contrast, a number of studies [ 3, 10, 13, 15, 16 ] have suggested deferring surgery until 6–8 weeks, because they found an increase in procedure and anaesthesia‐related morbidity and mortality in these patients. The problem in many of these studies was that all patients were taken up for surgery irrespective of their Ranson scoring and thus included even those patients who had severe disease.…”
Section: Discussionmentioning
confidence: 72%
“…A general surgeon treating a patient of ABP, if given the option, would probably still like to wait and perform an interval cholecystectomy after 6–8 weeks [ 3, 13 ]. However, our results of ELC when compared with the interval group showed no significant difference in any of the operative parameters or postoperative parameters except that there was significantly greater difficulty in dissection in the interval group.…”
Section: Discussionmentioning
confidence: 78%
“…A number of studies have reported equally good results whether urgent or early surgery' is performed without specifying the predicted severity of their pa tients [33][34][35], including at least one pro spective randomized trial [9]. In contrast, many other studies have shown a high mor tality (20-50%) with urgent surgery [11,15,16,36], There has only been one prospective randomised trial of urgent versus early sur gery' which used predictive severity criteria [10]. It was shown that in urgent surgery in predicted severe cases there was a morbidity in 19/28 (83%; 11 deaths or 48%) compared to 3/17 (18%; 2 deaths or 11%) in those undergoing surgery at a later time.…”
Section: Biliary Decompression: Surgical Versus Endoscopic Techniquesmentioning
confidence: 99%
“…This is not only necessary to arrest progressive pancreatitis, but can also be done without much risk [27].…”
Section: Treatment In the Acute Attackmentioning
confidence: 99%